THE INFLUENCE OF EMPLOYEE SELECTION ON WORK PRODUCTIVITY AT REYHAN SQUARE HOTEL SELAYAR ISLANDS DISTRICT - Putra Mandala Utama Muchtar; Sitti Nurbaya; Muhiddin Daweng (CV. AFDIFAL MAJU BERKAH, 2024)
HR development is not just about recruitment and training, but also involves career management, performance management, rewards, and inter-employee relations. Organizations that successfully build an inclusive culture and focus on employee development will create an environment where every individual feels valued and has opportunities to grow.The main objective of this study is to analyze the effect of employee selection on work productivity in the hotel industry. By analyzing the factors that influence employee selection as well as their impact on productivity, this research is expected to provide useful insights for HR practitioners in improving employee selection and management strategies. In addition, this research is also expected to contribute to the development of HR management theory. The population in this study was employees of the Reyhan Square Hotel which amounted to 40 people. The population used was also a sample in this study. Where the sampling technique used is saturated sampling. Saturated sampling is a sampling technique when all members of a population are used as samples. The method used in this study is quantitative, quantitative data that focuses on measuring and analyzing statistical number-based data. By using a survey method approach to find the cause and effect. The conclusion of this study, Variable X, namely Selection, has a positive and significant effect on the work productivity of Reyhan Square Hotel with a Selection coefficient (X) value of 0.437 and a calculated t value of 2,824 t table 2,024 with a significant value of 0.008 0.05.